Assessing the Share of Impaired Visual Function, Fine Motor Coordination and Visual-motor Integration in Dyslexic Children with the Eta/Mu Model - , Carlo Aleci; , Francesca Vai (Archives of Current Research International, 2019)
Aims: A computational model aimed to estimate the proportion of visual/motor deficits (first-order defects) and visual-motor abnormal integration (second-order defect) in dyslexic children is described. Study Design: Single-masked case-control study. Place and Duration of Study: Sample: Service of Neuro-Ophthalmology, University of Turin, between December 2017 and November 2018. Methodology: Twenty subjects (age 8-10) were administered a set of tests that recruit the visual and motor domain in different proportions. The score obtained in each trial is weighed by the correspondent share of visuoperceptive and motor recruitment. This way two indexes are obtained: Eta (h) and Mu (m), that quantify the expected and estimated damage of the two functions across the range of average performance. The difference between the expected and estimated level of damage in the two domains represents the quota of selective visuoperceptive / motor impairment of the subject. In turn, no or negligible difference in the presence of abnormal z-score would reveal impaired visual-motor integration with no evident visual or motor damage. Results: The model detected a prevalent first-order defect in the visuo perceptive or motor domain in 58% of the cases (visuo perceptive alteration: 27%, motor alteration: 73%), and a prevalent second-order defect in the remaining 42% of the subjects. Internal consistency was adequate for research and screening purpose (Cronbach’s coefficient alpha: from 0.77 to 0.84). Conclusion: The Eta/Mu model seems a promising tool to detect cases of visual and motor alteration as well as the level of visual-motor integration in dyslexic children. Further effort is needed to improve test-retest reliability by examining larger samples, so as to make it suitable to customize the rehabilitation program of children suffering from learning disabilities.